Growers’ knowledge on spices cultivation in Shibganj upazila under Bogura district (International Journal of Agricultural Research, Innovation and Technology, 2020)
The main objective guided the present study was to evaluate the knowledge of the growers on spices cultivation practice in Shibganj upazila under Bogura district. Three unions of the upazila were purposively selected based on the vicinity to the Spices Research Center, Bogura. Data were collected from selected growers using predesigned structured interview schedule. Eleven selected characteristics of the growers were considered as independent variables. As dependent variable, knowledge on spices cultivation practice was calculated by construction of a scale containing thirteen relevant questions. Coefficient of correlation was employed to determine the relationship between the selected characteristics of the growers and their knowledge on spices cultivation practice. Majority (67.8%) of the growers were middle aged, the highest portion (61.1%) of them belonged to primary level education. Major proportion (60.0%) of them had small family size, almost all of them (98.9%) possessed small to medium farm size, and huge majority (87.8%) of them earned up to BDT 240000 annually. About three-fourth (73.3%) of the farmers had medium extension contact, half of them (50.0%) had poor training experience while 40.0 percent of them had medium innovativeness. Great majority (85.5%) of the farmers had small to medium spices cultivation area (up to 0.6 ha) while almost three-fourth (72.2%) of them had medium to long durational (11 to above 20 years) practice of spices cultivation. Majority (65.6%) of them had moderate knowledge on spices cultivation technology compared to more than onefourth (26.7%) having high knowledge and only 7.7 percent had low knowledge on the same. None of the selected characteristics showed significant relationship with the knowledge on spices cultivation practice.Int. J. Agril. Res. Innov. Tech. 10(1): 102-107, June 2020